Development of The Vistori Book on Basic Concepts of Division for Grade II Elementary School Students - Aurelia, Davina; Linguistika, Yulia; Roebyanto, Goenawan; Nuraini, Ni Luh Sakinah (Universitas Negeri Malang, 2024)
The use of textual learning media in elementary school that can help to improve literacy and students' ability to understand stories is still limited, especially when it is integrated with mathematics. The goal of this study is to produce a vistori book on the topic of the basic concept of division for second grade elementary school that is assessed for validity. The ADDIE model, which consists of five phases such as analysis, design, development, implementation, and evaluation, was used in this study. In this research, data collection involved the utilization of interviews, questionnare, and documentation. The score obtained from expert validation and student responses were calculated using a quantitative descriptive methodology. The findings showed that vistori books get excellent qualifications for both validity and attractiveness. Based on analysis, vistori book media on the basic concept of division for second grade elementary school is qualified for use in learning.